Association between shift work and risk of type 2 diabetes mellitus: a systematic review and dose-response meta-analysis of observational studies. (2nd January 2020) - Gao, Yinyan; Gan, Ting; Jiang, Lili; Yu, Li; Tang, Daimao; Wang, Yihui; Li, Xiuxia; Ding, Guowu
ABSTRACT: To evaluate the association between shift work and risk of type 2 diabetes mellitus, we searched PubMed, EMBASE and Web of Science from their inception to June 8, 2019. Observational studies examining the relationship between shift work and type 2 diabetes were included. Subgroup analyses were conducted to explore whether specific characteristics would affect the relationship. A dose-response relationship was estimated by using generalized least squares trend regression. Finally, twelve cohort studies and nine cross-sectional studies were included (inter-rater agreement, k = 0.96). The result of meta-analysis indicated that shift work was associated with an increased risk of type 2 diabetes (relative risk = 1.10, 95% confidence interval = 1.05–1.14). Subgroup analyses demonstrated that female shift workers have increased risk of type 2 diabetes while male not observed, health care workers showed the highest risk compared with civil servants and manual workers, and night shift and rotating shift were associated with an increased risk of type 2 diabetes. Dose-response meta-analysis based on three cohorts among female workers indicated that there might be a positive association between duration of shift work and the risk of type 2 diabetes. In conclusion, shift work is positively associated with an increased risk of type 2 diabetes. Among female workers, with the years of exposure to shift work prolonged, the risk of type 2 diabetes might increase accordingly. In the future, more studies are needed to confirm the results of dose-response analysis.